Electrospun Amygdalin and Inula helenium Extract-loaded Polylactic acid (PLA)/Polyvinylpyrrolidone (PVP) Nanofibrous Patches for Colon Cancer Treatment: Fabrication, Characterization and Antitumour Effect Results - ŞAHİN, ALİ (My University, 2024)
in this study, 75PLA/25PVP nanofibrous loaded with amygdalin (AMG) andInula helenium(I.H) extract were produced by electrospinning method in order to prevent local colon cancer recurrence, and the effect of the produced nanofibrous on the HCT-116cell line was examined in vitro. When the scanning electron microscopy (SEM) images were examined, the fiber diameter of the 75PLA/25PVP group was measured as 443.74±79nm, but the addition ofI.Hand AMG caused a thickening effect on the fiber diameters. Drug release results show the controlled release period of 75PLA/25PVP/I.Hand 75PLA/25PVP/AMG loaded nanofibrous patches within 180h. Slowly degrading nanofibrous remained durable for up to 25 days. When the in vitro cytotoxicity results were analyzed, all nanofibrous were found to be effective in inducing cytotoxicity against HCT-116 colon cancer cells. The most effective group is the group in whichI.Hextract and AMG drug are loaded onto the nanofibrous together. AMG drug andI.Hplant extract showed effects on the colon cancer cell line in in vitro experiments. Considering all the results I.H and AMG loaded nanofibrous can be implanted into solid tumor cells in order to reduce the risk of local recurrence of cancer after surgery in colon cancer.
Keywords: Sağlık Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Health Sciences; Natural Sciences; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Colon cancer; Plant extract; Amygdalin; Nanofibrous patch; PLA; PVP